Decolonising public administration : a case of Limpopo Education Department - Modiba, N. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
This paper examines whether decolonising the Limpopo Education Department would not enable the department to match or outsmart its competitors in terms of education delivery. The paper is conceptual and empirical in nature within the qualitative research paradigm. The question guiding the paper is: how many years does the province require to become the pace-setter of good education delivery in the country? Narrative enquiry and interviewing techniques were used to collect data. Out of the population of 15 experienced sectional heads in the education department in Limpopo Province, South Africa, 6 were conveniently sampled. The sampled research participants were all heads of sections. Findings revealed that ignoring to dispense knowledge with liberating force delays the departmental decolonisation; secondly, untransformed organisational structures are a setback for the department; thirdly, applying antiquated governance procedures robs the department of the opportunity to revamp through decolonising; fourthly, lack of modernity; lastly, un-implemented impressive policies. The researcher recommends for the disruption and dismantling of colonialist practices.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Governance; Liberating; Policies; Systems; Untransformed; Education -- South Africa -- Limpopo; Public administration -- South Africa -- Limpopo; Corporate governance -- South Africa -- Limpopo